Determination of objects contours using physical principles - Patrícia C. T. Gonçalves (2008)
Segmentation, the identification of an object represented in a static image or along image sequences, is one of the most common and complex tasks in the domain of Computational Vision. Usually, whenever we intend to extract higher level information from images, we need to start by segmenting them. The main goal of this work is to segment an object represented in an image by extracting its contour after defining an initial contour for it; this coarse contour will evolve along an iterative process until it reaches the frontier of the desired object, figure 1. For that purpose, a deformable model is used, whose behaviour is driven by physical principles.